Significance of RPG Game in Learning of Reading Comprehension for Beginner BIPA Learners - Renda Yuriananta (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
Product development in this article produces learning media to practice reading comprehension skill based RPG Game for beginner BIPA students. The model used in developing the product is the adaptation of Borg and Gall model. Adaptation of the model is done by converting ten stages into eight stages only. Based on product trial conducted, the final product validation result in BIPA experts is 98.44%, BIPA learning experts is 78.13%, and the learning media expert is 83.82 %. The final product validation result for BIPA students is 97.92% and 97.22%. Based on these results, the product is classified as very feasible and can be implemented.